Pengaruh Spiritualitas terhadap Subjective Well Being Mahasiswa Tingkat Akhir - Nancy Lolo Arung; Yonathan Aditya (Konsorsium Psikologi Ilmiah Nusantara, 2021)
Senior year students who are working on their thesis as one of the requirements to graduate, may experience pressure which cause stress and depression. The arise of stress and depression in senior year students can cause a low subjective well-being thus it may affect the performance of the thesis. It is considered that spirituality can affect level of subjective well-being of students because with individual spirituality, they are able to feel the presence of God and to obtain social support during the difficult times. Hence, this research is conducted with aims to know the effect of spirituality toward subjective well-being of university students. This research uses quantitative method with purposive sampling technique which conducted to 150 senior year students. The measuring instrument used in this research is SHALOM (?=.91), SPANE (?=.87, ?=.78) and SWLS (?=.82). The result of this research shows a significant effect between spirituality toward subjective well-being (? = .22, p < .05), meaning that the higher the spirituality level of the students, the higher the subjective well-being level of that students.